D154Q Mutation does not Alter KRAS Dimerization. Issue 2 (30th January 2022) - Grozavu, Ingrid; Stuart, Sarah; Lyakisheva, Anna; Yao, Zhong; Pathmanathan, Shivanthy; Ohh, Michael; Stagljar, Igor
Graphical abstract: Highlights: Ambrogio et al. found KRAS D154Q as a dimer-deficient mutant. They used this variant to study the role of dimerization in KRAS oncogenic behaviour. Using 3 different PPI assays, we found that KRAS D154Q still homo and heterodimerized. We caution using D154Q mutation to study the role of dimerization in oncogenic KRAS. Abstract: KRAS is one of the most frequently mutated oncogenes in human cancers. Despite nearly 40 years of research, KRAS remains largely undruggable, in part due to an incomplete understanding of its biology. Recently, KRAS dimerization was discovered to play an important role in its signalling function. The KRAS D154Q mutant was described as a dimer-deficient variant that can be used to study the effect of dimerization in KRAS oncogenicity. However, we show here that KRAS D154Q homo- and heterodimerized with KRAS WT using three separate protein–protein interaction assays, and that oncogenic KRAS dimerization was not negatively impacted by the presence of a secondary D154Q mutation. In conclusion, we advise caution in using this variant to study the purpose of dimerization in KRAS oncogenic behaviour.